Riqueza e distribuição espacial de formigas cortadeiras (Hymenoptera: Formicidae) em eucaliptais em biomas mata atlântica e cerrado em Minas Gerais - Arhnold, Alexandre (2017)
Eucalyptus plantations are the most important in Brazilian forestry sector . The leaf-cutting ants of genus Atta and Acromyrmex are your main pests. Species of these genera are distributed by all Brazilian states, but there are no current records of which and how many species of these ants are associated with the Eucalyptus plantations, nor how environmental variables influence on occurrence of this species. Samples of leaf-cutting ants were made in eucalyptus plantations in the biomes Mata Atlântica and Cerrado in Minas Gerais State. The main objective was to identify the species of leaf-cutting ants associated with eucalyptus plantations in these biomes. Additionally, your spatial distribution patterns, population density and frequency were checked and the environmental variables influence (altitude, clay soil content, maximum air temperature and minimum air temperature) on their probability of occurrence was evaluated. Nine species and three subspecies associated with the eucalyptus crop were found. Acromyrmex niger had the highest population density and Acromyrmex subterraneus molestans had the highest frequency in eucalyptus plantations at the Mata Atlântica biome. Atta sexdens had the highest population density and frequency in Cerrado biome. The predominant spatial distribution has aggregated. The altitude negatively influenced the occurrence of Atta sexdens and Acromyrmex niger. The maximum air temperature positively influenced the occurrence of Atta laevigata and negatively the occurrence of Acromyrmex niger and Acromyrmex subterraneus molestans. The clay soil content negatively influenced the occurrence of Acromyrmex subterraneus brunneus and positively the occurrence of Acromyrmex niger.